Aphelochaeta (Polychaeta: Cirratulidae) from the Pacific coast of Costa Rica, with a description of five new species - Dean, Harlan K.; Blake, James A. (Zootaxa, 2016)
Five new species of bitentaculate Cirratulidae belonging to the genus Aphelochaeta are herein described from the Pacific coast of Costa Rica, all from shallow subtidal depths. Aphelochaeta antelonga sp. nov. is characterized by a long biannulate peristomium and fibrillated capillary setae and is from 11–18 m in the Gulf of Nicoya. Aphelochaeta guimondi sp. nov., with a wide dorsal trough in the thorax and hirsute capillaries (visible using SEM), is described from 11–26 m in the Gulf of Nicoya. Aphelochaeta praeacuta sp. nov., with its first peristomial annulation extending as a dorsal crest over the second annulation and first setiger, was collected from 11–28 m in Bahia Culebra. Aphelochaeta striata sp. nov., collected from 11–28 m in the Gulf of Nicoya, is recognized by its narrow body and the transverse blue stripes across the venter of setigers 5–8 produced with methyl green stain. Aphelochaeta zebra sp. nov., collected from a coral reef in Golfo Dulce, is characterized by its expanded posterior end and the darkly staining intersegmental regions using methyl green stain. Additionally, A. glandaria Blake, 1996, a species reportedly with a widespread geographic distribution (Blake, 1996), was also encountered subtidally from the Gulf of Nicoya and Golfo Dulce.